2022
DOI: 10.1097/won.0000000000000873
|View full text |Cite
|
Sign up to set email alerts
|

Moisture-Associated Skin Damage

Abstract: Moisture-associated skin damage (MASD) occurs when skin is repeatedly exposed to various sources of bodily secretions or effl uents, often leading to irritant contact dermatitis, characterized by infl ammation with or without denudation of affected skin. In 2020, the Wound, Ostomy and Continence Nurses Society commissioned an initiative that led to the addition of multiple International Classifi cation of Diseases, Tenth Revision, Clinical Modifi cation codes ( ICD -10-CM ) for irritant contact dermatitis caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
0
9
0
3
Order By: Relevance
“…11 Patients with intestinal ostomies are susceptible to erosion and secondary infection of peristomal skin caused by the liquid fecal stoma effluent rich in digestive enzymes and intestinal bacteria. 4,12 Maintenance of peristomal skin health relies on a pouching system that ensures continuous contact between the skin barrier and the skin around the stoma. 7 In this case, Baby Q was not managed using a pouching system and was exposed to a large amount of exudate on the peristomal skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Patients with intestinal ostomies are susceptible to erosion and secondary infection of peristomal skin caused by the liquid fecal stoma effluent rich in digestive enzymes and intestinal bacteria. 4,12 Maintenance of peristomal skin health relies on a pouching system that ensures continuous contact between the skin barrier and the skin around the stoma. 7 In this case, Baby Q was not managed using a pouching system and was exposed to a large amount of exudate on the peristomal skin.…”
Section: Discussionmentioning
confidence: 99%
“…3 Peristomal moisture-associated skin damage (MASD), a form of irritant contact dermatitis that occurs when the peristomal skin is exposed to effluent from an intestinal ostomy or urostomy, is particularly prevalent. 4 It affects 34% of people with ileostomies. 5 One study revealed those living with an ileostomy were more likely to experience peristomal MASD than those with a colostomy.…”
Section: Introductionmentioning
confidence: 99%
“…• uszkodzenia skóry związane z wilgocią w okolicy stomii (peristomal moisture-associated skin damage -PMASD), • urazy skóry związane z przylepcem medycznym (peristomal medical adhesive-related skin injury -PMARSI) [12,15,16]. Zmiany z grupy PMASD powstają w wyniku podrażnienia przez utrzymującą się na skórze wokół stomii wilgoć.…”
Section: Wstępunclassified
“…1). W zależności od charakteru wydzieliny i czasu jej oddziaływania na skórę zmiana przybiera postać zaczerwienienia, nadżerek, częściowej utraty skóry z nieregularnymi granicami, utraty pełnej grubości skóry ze zwiększonym wysiękiem surowiczym i krwawieniem, którym towarzyszy uczucie swędzenia, pieczenia i bólu [12,15].…”
Section: Wstępunclassified
See 1 more Smart Citation